PENGARUH PENDAPATAN NASIONAL PERKAPITA TERHADAP JUMLAH UANG BEREDAR (M1) Dl INDONESIA - Eka Safitri; M Basir Kimin; Enny Muhaini Hanafiah (Department of Development Economics, Universitas Sriwijaya, 2003)
Economic growth in a country is reflected from national income. Income.of the society is reflected from the national income of capita and can influence the money supply which if income increase will influence the society to consume, it is reflected from the purchasing power. 1he money supply, in this case, includes the currency and Demand Deposit (DD) or M1. Income and money supply have close relation about 67,7%, it reflects from correlation or is 0,677. The determinant coefficient is 45,90%, it means that 45,9% change of money supply causes by income and the rest about 54,1% influenced by the other variables. Therefore the increase of money supply in Indonesia (1990-2001) it caused by income and by the economic factors but also caused by non-economic factors. The suggestion is Bank Indonesia have to control the economic activity by using the instn1ment of their policy and it will increase the income of society. Keywords: Income of per Capita. Money, Supply